Basidiomycete‐specific PsCaMKL1 encoding a CaMK‐like protein kinase is required for full virulence of Puccinia striiformis f. sp. tritici. (14th September 2017) - Jiao, Min; Yu, Dan; Tan, Chenglong; Guo, Jia; Lan, Dingyun; Han, Ershang; Qi, Tuo; Voegele, Ralf Thomas; Kang, Zhensheng; Guo, Jun
Summary: Calcium/calmodulin‐dependent kinases (CaMKs) are Ser/Thr protein kinases (PKs) that respond to changes in cytosolic free Ca 2+ and play diverse roles in eukaryotes. In fungi, CAMKs are generally classified into four families CAMK1, CAMKL, RAD53 and CAMK‐Unique. Among these, CAMKL constitutes the largest family. In some fungal plant pathogens, members of the CaMKL family have been shown to be responsible for pathogenesis. However, little is known about their role(s) in rust fungi. In this study, we functionally characterized a novel PK gene, PsCaMKL1, from Puccinia striiformis f. sp. tritici ( Pst ). Ps CaMKL1 belongs to a group of PKs that is evolutionarily specific to basidiomyceteous fungi. Ps CaMKL1 shows little intra‐species polymorphism between Pst isolates. PsCaMKL1 transcripts are highly elevated at early infection stages, whereas gene expression is downregulated in barely germinated urediospores under KN93 treatment. Overexpression of PsCaMKL1 in fission yeast increased resistance to environmental stresses. Knock down of PsCaMKL1 using host‐induced gene silencing (HIGS) reduced the virulence of Pst accompanied by reactive oxygen species (ROS) accumulation and a hypersensitive response. These results suggest that Ps CaMKL1 is a novel pathogenicity factor that exerts it virulence function by regulating ROS production in wheat.